Breeding for resistance to necrosis inducing strains of common bean mosaic virus - Gridley, Howard E. (International Center for Tropical Agriculture, 1994)
Bean common mosaic virus (BCMV) is seed transmitted and the most important virus disease of beans in Africa. A breeding programme was initiated in 1990 in Uganda to develop lines with resistance to necrotic strains that predominate in the continent. Evaluation of field layout on infection level showed increased within row spacing gave a significantly higher level and is used for all resistance screening. Multisite yield testing of lines derived from introductions and selection in introduced populations has identified resistant material, differing for seed size and growth habit, with seed yields markedly exceeding the released cultivars. Small seeded lines exhibited the heaviest yield and their adoption could significantly contribute to increased production. Genotype x environment interactions for seed yield were frequent in the multisite yield trials. A breakdown of these interactions suggested that crossover or qualitative interactions predominated and indicated means to refine yield testing strategies